A domotic system with remote access based on web services - Pardo, Mauricio Esteban (2008)
Domotics systems are intelligent systems for houses and apartments to control several issues as security and light or climate devices. In this work we present the development of an economic domotic system to control different electrical devices in a private house. This is achieved either from inside the building or by remote control using a regular Internet connection. In order to provide this functionality, the system includes a server that provides web services to the controlling applications in the house. This server also offers an interface that uses AJAX to optimize device handling.